Chloride channel accessory 1 integrates chloride channel activity and mTORC1 in aging‐related kidney injury. Issue 7 (12th June 2021) - Lee, Hak Joo; Donati, Andrew; Feliers, Denis; Sun, Yuyang; Ding, Yanli; Madesh, Muniswamy; Salmon, Adam B.; Ikeno, Yuji; Ross, Corinna; O'Connor, Christopher L.; Ju, Wenjun; Bitzer, Markus; et al.
Abstract: The mechanism of kidney injury in aging are not well understood. In order to identify hitherto unknown pathways of aging‐related kidney injury, we performed RNA‐Seq on kidney extracts of young and aged mice. Expression of chloride (Cl) channel accessory 1 (CLCA1) mRNA and protein was increased in the kidneys of aged mice. Immunostaining showed a marked increase in CLCLA1 expression in the proximal tubules of the kidney from aged mice. Increased kidney CLCA1 gene expression also correlated with aging in marmosets and in a human cohort. In aging mice, increased renal cortical CLCA1 content was associated with hydrogen sulfide (H2 S) deficiency, which was ameliorated by administering sodium hydrosulfide (NaHS), a source of H2 S. In order to study whether increased CLCA1 expression leads to injury phenotype and the mechanisms involved, stable transfection of proximal tubule epithelial cells overexpressing human CLCA1 (hCLCA1) was performed. Overexpression of hCLCA1 augmented Cl − current via the Ca ++ ‐dependent Cl − channel TMEM16A (anoctamin‐1) by patch‐clamp studies. hCLCA1 overexpression also increased the expression of fibronectin, a matrix protein, and induced the senescence‐associated secretory phenotype (SASP). Mechanistic studies underlying these changes showed that hCLCA1 overexpression leads to inhibition of AMPK activity and stimulation of mTORC1 as cellular signaling determinants of injury. Both TMEM16A inhibitor and NaHS reversed these signaling events and prevented changes in fibronectin and SASP. We conclude that CLCA1‐TMEM16A‐Cl − current pathway is a novel mediator of kidney injury in aging that is regulated by endogenous H2 S. Abstract : Chloride channel accessory 1 expression is increased in the tubular epithelial cells of aged kidneys. In vitro experiments show that CLCA1 augments the activity of TMEM16A, a Ca++‐dependent Chloride Channel, activates mTORC1, augments the synthesis of matrix proteins, and induces SASP, whcih contribute to aging associated kidney injury.